Difference and Factor Associated with Interferon Gamma Level in Pulmonary Tuberculosis Patients and Healthy Control - Sinaga, Bintang Yinke Magdalena; Tarigan, Amira Permatasari (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND : Interferon-gamma (INF-γ) is an important cytokine in the immune response against Mycobacterium tuberculosis. Interferon-gamma activates macrophage to kill intracellular mycobacterium. AIM: The aim of this study is to determine the difference of plasma INF-γ level in pulmonary tuberculosis (PTB) patients compared to a healthy control and factors associated with interferon-gamma level. METHODS: This is a case–control study. Fifty subjects were selected, including 25 new PTB patients with positive sputum smear, and 25 healthy control (non TB patients) with no symptoms of tuberculosis, normal chest X-Ray and no history of previous tuberculosis. Interferon-gamma concentration was determined by an ELISA technique. Data were analyzed with independent t-test and the results were statistically significant at p < 0.05. RESULTS: Interferon-gamma level was significantly higher in PTB patients compared to healthy control (p = 0.024). Mean ± SD interferon gamma level was 317.2 ± 201.97 pg/ml in PTB patients and 213.5 ± 86.43 pg/ml in healthy control. Acid fast bacilli (AFB) positivity was significantly associated with interferon gamma level (p < 0.001). Interferon gamma level in TB patients with AFB 1+ was 503.22 ± 146.15 pg/ml, AFB 2+ was 337 ± 81.61 pg/ml, and AFB 3+ was 88.27 ± 51.32 pg/ml. Sex, body mass index (BMI), and age were not associated with INF-γ level. CONCLUSIONS: Interferon gamma level was significantly higher in PTB patients than healthy control. Sex, BMI, and age were not associated with INF-γ level. Interferon-gamma level was significantly associated with AFB positivity in pulmonary tuberculosis patients.